IMPLEMENTATION OF MAQASID AL-SHARIAH ON SUBROGATION IN MUSYARAKAH MUTANAQISAH CONTRACTS DECIDED BY THE GENERAL COURT - Muchammad Chaqqul Amin (Universitas Muhammadiyah Surabaya, 2026)
The development of Islamic economic transactions in Indonesia has increased the legal complexity of financing disputes, including disputes arising from Musyarakah Mutanaqisah contracts. Positive law places Islamic economic disputes within the absolute jurisdiction of the Religious Courts; however, Surabaya District Court Decision Number 311/Pdt.G/2021/PN. Sby adjudicated a dispute involving subrogation connected to a Musyarakah Mutanaqisah financing contract. This article examines the jurisdictional context of the case, the application of subrogation in Musyarakah Mutanaqisah within Islamic legal principles, and the extent to which the decision aligns with maqasid al-shariah. This research employs normative legal research, utilizing statutory, case, conceptual, and comparative approaches. The findings show that the case should have been examined by the Religious Court because the disputed legal relationship was rooted in Islamic financing, namely Musyarakah Mutanaqisah and sharia-based subrogation. The decision produced a degree of asset-related settlement, but it did not fully satisfy Hifz al-Din because the case was resolved by a forum that lacked absolute jurisdiction over Islamic economic disputes. The article argues that stronger coordination between the General Courts and Religious Courts is needed to prevent forum error and to secure legal certainty, sharia compliance, and substantive justice in Islamic financing disputes.